Fireproof coating with high water resistance and corrosion resistance and preparation method thereof
By optimizing the formulation, film-forming substances such as aqueous epoxy resin, pure acrylic emulsion, polyurethane emulsion, and combined with silicone modified ammonium polyphosphate and other ingredients, an expanded carbon layer is formed at high temperature, solving the shortcomings of existing fire-resistant coatings in terms of water resistance and corrosion resistance, and achieving efficient fire-resistant, waterproof and corrosion-resistant effects.
Patent Information
- Application Number
- CN202411965798.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing steel structure fire-retardant coatings have shortcomings in water resistance and corrosion resistance, making it difficult to effectively isolate heat and oxygen in high temperature environments, and delay or prevent the spread of flames.
By optimizing the formulation, aqueous epoxy resin, pure acrylic emulsion, and polyurethane emulsion are used as film-forming substances, and combined with silicone modified ammonium polyphosphate, dipentaerythritol, melamine and graphene oxide-polyacrylic acid-nano silica composites and other components, an expanded carbon layer is formed at high temperature to prevent the flame from spreading, while improving the waterproof and corrosion resistance of the coating.
It realizes the formation of an effective expanded carbon layer under high temperature environments, prevents the spread of flames, and significantly improves the waterproof and corrosion resistance of the paint, ensuring that the steel structure maintains its load-bearing capacity during fires.
Smart Images

Figure BDA0005218317440000081 
Figure BDA0005218317440000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fire retardant coatings, and in particular relates to a highly waterproof and corrosion-resistant fire retardant coating and a preparation method thereof. Background Art
[0002] Steel structure fire retardant coating is a coating specially used to improve the fire resistance of steel structures. Although steel itself will not burn, its mechanical properties (such as yield point, tensile strength and elastic modulus) will drop sharply in high temperature environments. In order to prevent steel structures from losing their bearing capacity in fires, steel structure fire retardant coatings are widely used in buildings and other engineering structures. These coatings can form a fire-resistant and heat-insulating protective layer when a fire occurs, thereby improving the fire resistance limit of steel structures.
[0003] Steel structure fire retardant coatings are mainly composed of the following components:
[0004] 1. Film-forming substance: It not only ensures that the coating has various functions under normal conditions, but also has flame retardancy and excellent expansion and foaming properties under flame or high temperature conditions.
[0005] 2. Catalyst: A substance that can decompose phosphoric acid under certain conditions. The decomposed acid dehydrates the polyol, thereby forming a carbonized layer with a non-flammable three-dimensional spatial structure.
[0006] 3. Carbon forming agent: It is the material basis for the coating to form a foam carbonized layer with a non-flammable three-dimensional spatial structure at high temperature, and it acts as a skeleton for the foam carbonized layer.
[0007] 4. Foaming agent: Only under the action of the foaming agent can the expansion layer be produced under high temperature flames. The foaming agent decomposes when exposed to fire and releases non-combustible gases such as ammonia, water, carbon dioxide, and hydrogen halide, causing the coating to foam and expand when it reaches the softening point, forming a sponge-like structure.
[0008] Although the existing steel structure fire retardant coatings have the advantages of good fire resistance, strong durability, and convenient construction, their water resistance and corrosion resistance need to be improved. Summary of the invention
[0009] The present invention aims to provide a highly waterproof and corrosion-resistant fire-retardant coating and a preparation method thereof. By optimizing the formula, the coating can form an expanded carbon layer at high temperature, effectively isolating heat and oxygen, delaying or preventing the spread of flames, and making the fire-retardant coating have high fireproof performance and achieve high waterproof and corrosion resistance effects.
[0010] The technical solution adopted by the present invention to achieve its purpose is as follows:
[0011] A highly waterproof and corrosion-resistant fireproof coating comprises, by weight, 20-25 parts of waterborne epoxy resin, 10-15 parts of pure acrylic emulsion, 5-10 parts of polyurethane emulsion, 15-20 parts of organosilicon-modified ammonium polyphosphate, 8-10 parts of dipentaerythritol, 6-8 parts of melamine, 3-5 parts of graphene oxide-polyacrylic acid-nano silicon dioxide composite, 8-12 parts of pigments and fillers, 4-6 parts of zinc phosphate, 4-6 parts of additives and 8-10 parts of water.
[0012] Preferably, the graphene oxide-polyacrylic acid-nano silicon dioxide composite is prepared by the following method:
[0013] S1. dispersing graphene oxide in deionized water, ultrasonically dispersing, to obtain a graphene oxide dispersion; adding a silane coupling agent thereto, stirring and reacting at 60-70° C. for 4-6 hours, to obtain graphene oxide treated with a silane coupling agent;
[0014] S2. The graphene oxide treated with a silane coupling agent is dispersed in deionized water, a polyacrylic acid solution having a mass concentration of 5-7% is added, and the reaction is stirred at 60-70° C. for 6-8 hours to obtain a graphene oxide-polyacrylic acid composite;
[0015] S3. Disperse nano-silica in deionized water and ultrasonically disperse it to obtain a nano-silica dispersion; disperse graphene oxide-polyacrylic acid complex in deionized water and ultrasonically disperse it to obtain a graphene oxide-polyacrylic acid complex dispersion, mix it with the nano-silica dispersion, stir and react at 60-70°C for 4-6h, centrifuge, wash with deionized water, and dry to obtain a graphene oxide-polyacrylic acid-nano-silica complex.
[0016] Preferably, the ultrasonic dispersion time is 1-2 h.
[0017] Preferably, the amount of the silane coupling agent used is 1-2% of the mass of the graphene oxide.
[0018] Preferably, the pigment filler is selected from one or more of silicate, aluminum hydroxide, magnesium hydroxide, aluminum oxide, zinc borate, expanded graphite, and nano clay.
[0019] Preferably, the auxiliary agent includes one or more of a thickener, a leveling agent, a dispersant, and a toughening agent.
[0020] A method for preparing a highly waterproof and corrosion-resistant fire-retardant coating comprises the following steps:
[0021] A. Premixing: Add water-based epoxy resin, pure acrylic emulsion, polyurethane emulsion and water into the reactor and stir evenly;
[0022] B. Filler dispersion: add organosilicon-modified ammonium polyphosphate, dipentaerythritol, and melamine to the premixed solution, and stir at high speed; then add graphene oxide-polyacrylic acid-nanosilica composite, zinc phosphate, pigments and fillers, and additives to the premixed solution, and stir at high speed to obtain a coating;
[0023] C. Filtration and packaging: Filter the prepared coating to remove impurities, and package and store.
[0024] Preferably, the stirring rate of high-speed stirring is 800-2000 r / min, and the stirring time is 1-3 h.
[0025] The beneficial effects of the present invention are:
[0026] The present invention adopts water-based epoxy resin, pure acrylic emulsion, and polyurethane emulsion as film-forming substances, which not only have good film-forming ability, but also can match the decomposition temperature of the PNC system, and cooperate with the expansion flame retardant system to form a porous expansion layer when exposed to high temperature or fire, thereby preventing the rapid heating of the steel structure. The polyurethane emulsion in the film-forming substance can increase the toughness of the coating and prevent the phenomenon of "hot brittle and cold sticky". At the same time, the addition of polyurethane emulsion and water-based epoxy resin improves the water resistance of the coating. The coating forms a dense surface after curing, which can effectively block water penetration and significantly improve the waterproof performance of the coating. The water-based epoxy resin in the film-forming substance can also improve the adhesion between the coating and the steel plate and improve the strength of the carbon layer. The three are used together to effectively cover the non-combustible gas released by the flame retardant system and increase the expansion ratio of the carbon layer.
[0027] Organosilicon-modified ammonium polyphosphate, dipentaerythritol and melamine form a flame retardant system. Organosilicon-modified ammonium polyphosphate acts as an acid source, decomposes at high temperature, releases phosphoric acid, promotes the dehydration and carbonization of the carbon source (dipentaerythritol), and forms a carbon layer. Melamine acts as a gas source, decomposes at high temperature to release gas (such as ammonia), which expands the carbon layer and forms a porous and dense insulation layer, thereby achieving the effect of flame retardancy and fire prevention. Among them, ammonium polyphosphate is modified with organosilicon to reduce its hygroscopicity, which provides a basis for the high waterproofness of the fire retardant coating.
[0028] The graphene oxide-polyacrylic acid-nano-silica composite contains graphene oxide and nano-silica, which is hydrophobic and can enhance the waterproof performance of the coating. At the same time, the composite fills the micropores in the coating to improve the density of the coating and prevent water and corrosive ions from penetrating into the coating, thereby enhancing the waterproof effect and corrosion resistance. On the other hand, the graphene oxide-polyacrylic acid-nano-silica composite plays a reinforcing role in the carbon layer, which can improve the mechanical strength and thermal insulation performance of the carbon layer, thereby further improving the fire resistance and durability of the coating.
[0029] Pigments and fillers are used to adjust the color and hiding power of the coating, and may also have a certain auxiliary effect on fire resistance. Additives improve the leveling, dispersibility and stability of the coating, ensuring construction performance and coating quality.
[0030] Zinc phosphate is added as an anti-rust pigment to improve the corrosion resistance of the coating. DETAILED DESCRIPTION
[0031] The raw materials used in the present invention are all purchased from the market, and the parts not described in the present invention are all prior art. The present invention is described in detail below in conjunction with specific embodiments and performance tests.
[0032] Example 1
[0033] Preparation of graphene oxide-polyacrylic acid-nanosilica composite:
[0034] The mass ratio of graphene oxide, nano-silicon dioxide and polyacrylic acid is 1:2:3. The specific preparation process is as follows:
[0035] S1. dispersing graphene oxide in deionized water, ultrasonically dispersing for 1 hour, to obtain a graphene oxide dispersion; adding 2% of the mass of graphene oxide silane coupling agent KH-550 thereto, stirring and reacting at 60° C. for 4 hours, after the reaction is completed, centrifuging, washing with deionized water, removing unreacted silane coupling agent, and obtaining graphene oxide treated with silane coupling agent;
[0036] S2. The graphene oxide treated with a silane coupling agent is dispersed in deionized water, a polyacrylic acid solution having a mass concentration of 6% is added, and the reaction is stirred at 60° C. for 8 h. After the reaction is completed, the graphene oxide is centrifuged and washed with deionized water to obtain a graphene oxide-polyacrylic acid composite;
[0037] S3. Disperse nano-silica in deionized water and ultrasonically disperse it for 1 hour to obtain a nano-silica dispersion; disperse the graphene oxide-polyacrylic acid complex in deionized water and ultrasonically disperse it to obtain a graphene oxide-polyacrylic acid complex dispersion, mix it with the nano-silica dispersion, stir and react at 60°C for 4 hours, centrifuge, wash with deionized water, and dry to obtain a graphene oxide-polyacrylic acid-nano-silica complex.
[0038] Example 2
[0039] A highly waterproof and corrosion-resistant fireproof coating comprises, by weight, 20 parts of water-based epoxy resin, 13 parts of pure acrylic emulsion, 8 parts of polyurethane emulsion, 15 parts of organosilicon-modified ammonium polyphosphate, 8 parts of dipentaerythritol, 6 parts of melamine, 3 parts of graphene oxide-polyacrylic acid-nano silicon dioxide composite, 5 parts of potassium silicate, 2 parts of magnesium hydroxide, 1 part of zinc borate, 4 parts of zinc phosphate, 1 part of leveling agent, 2 parts of dispersant, 1 part of toughening agent and 8 parts of water.
[0040] Example 3
[0041] A highly waterproof and corrosion-resistant fireproof coating comprises, by weight, 25 parts of water-based epoxy resin, 10 parts of pure acrylic emulsion, 10 parts of polyurethane emulsion, 20 parts of organosilicon-modified ammonium polyphosphate, 10 parts of dipentaerythritol, 8 parts of melamine, 5 parts of graphene oxide-polyacrylic acid-nano silicon dioxide composite, 6 parts of potassium silicate, 3 parts of aluminum hydroxide, 1 part of zinc borate, 6 parts of zinc phosphate, 2 parts of leveling agent, 2 parts of dispersant, 1 part of toughening agent and 10 parts of water.
[0042] Example 4
[0043] A highly waterproof and corrosion-resistant fireproof coating comprises, by weight, 23 parts of waterborne epoxy resin, 15 parts of pure acrylic emulsion, 5 parts of polyurethane emulsion, 17 parts of organosilicon-modified ammonium polyphosphate, 9 parts of dipentaerythritol, 7 parts of melamine, 4 parts of graphene oxide-polyacrylic acid-nano silicon dioxide composite, 6 parts of potassium silicate, 4 parts of magnesium hydroxide, 2 parts of zinc borate, 5 parts of zinc phosphate, 2 parts of leveling agent, 2 parts of dispersant, 2 parts of toughening agent and 9 parts of water.
[0044] Example 5
[0045] The highly waterproof and corrosion-resistant fire-retardant coatings of the above-mentioned embodiments 2-3 are all prepared by the following method, comprising the following steps:
[0046] A. Premixing: Add water-based epoxy resin, pure acrylic emulsion, polyurethane emulsion and water into the reactor and stir evenly;
[0047] B. Filler dispersion: add organosilicon-modified ammonium polyphosphate, dipentaerythritol and melamine to the premixed solution, and stir at a high speed of 100 r / min for 1 hour; then add graphene oxide-polyacrylic acid-nanosilica composite, zinc phosphate, pigment filler and additives to the premixed solution, and stir at a high speed of 1500 r / min for 3 hours to obtain the coating;
[0048] C. Filtration and packaging: Filter the prepared coating to remove impurities, and package and store.
[0049] Comparative Example 1
[0050] A highly waterproof and corrosion-resistant fireproof coating comprises, by weight, 20 parts of waterborne epoxy resin, 13 parts of pure acrylic emulsion, 8 parts of polyurethane emulsion, 15 parts of organosilicon-modified ammonium polyphosphate, 3 parts of graphene oxide, 8 parts of dipentaerythritol, 6 parts of melamine, 5 parts of potassium silicate, 2 parts of magnesium hydroxide, 1 part of zinc borate, 4 parts of zinc phosphate, 1 part of leveling agent, 2 parts of dispersant, 1 part of toughening agent and 8 parts of water. The preparation method is the same as that of Example 5.
[0051] Comparative Example 2
[0052] A highly waterproof and corrosion-resistant fireproof coating comprises, by weight, 20 parts of waterborne epoxy resin, 13 parts of pure acrylic emulsion, 15 parts of organosilicon-modified ammonium polyphosphate, 8 parts of dipentaerythritol, 6 parts of melamine, 3 parts of nano-silicon dioxide, 5 parts of potassium silicate, 2 parts of magnesium hydroxide, 1 part of zinc borate, 4 parts of zinc phosphate, 1 part of leveling agent, 2 parts of dispersant, 1 part of toughening agent and 8 parts of water. The preparation method is the same as that of Example 5.
[0053] Comparative Example 3
[0054] A highly waterproof and corrosion-resistant fireproof coating comprises, by weight, 20 parts of waterborne epoxy resin, 13 parts of pure acrylic emulsion, 15 parts of organosilicon-modified ammonium polyphosphate, 8 parts of dipentaerythritol, 6 parts of melamine, 2 parts of nano-silicon dioxide, 1 part of graphene oxide, 5 parts of potassium silicate, 2 parts of magnesium hydroxide, 1 part of zinc borate, 4 parts of zinc phosphate, 1 part of leveling agent, 2 parts of dispersant, 1 part of toughening agent and 8 parts of water. The preparation method is the same as that of Example 5.
[0055] Comparative Example 4
[0056] A highly waterproof and corrosion-resistant fireproof coating comprises, by weight, 20 parts of waterborne epoxy resin, 13 parts of pure acrylic emulsion, 15 parts of organosilicon-modified ammonium polyphosphate, 8 parts of dipentaerythritol, 6 parts of melamine, 3 parts of graphene oxide-polyacrylic acid-nano silicon dioxide composite, 5 parts of potassium silicate, 2 parts of magnesium hydroxide, 1 part of zinc borate, 4 parts of zinc phosphate, 1 part of leveling agent, 2 parts of dispersant, 1 part of toughening agent and 16 parts of water. The preparation method is the same as that of Example 5.
[0057] Test Example 1
[0058] The basic performance test of outdoor steel structure fire retardant coating refers to GB14907-2018 "Steel Structure Fire Retardant Coating", and the results are shown in Table 1.
[0059] Table 1
[0060]
[0061] Test Example 2
[0062] Water resistance test: The coating samples were immersed in water for 5 days, and the changes on the surface and edges of the coating were observed. The results are shown in Table 2.
[0063] Table 2
[0064] deal with Smear Change Example 2 No blistering, no shedding, no discoloration Example 3 No blistering, no shedding, no discoloration Example 4 No blistering, no shedding, no discoloration Comparative Example 1 Obvious bubbling, no shedding, no discoloration Comparative Example 2 Obvious bubbling, no shedding, no discoloration Comparative Example 3 Slight bubbling, no shedding, no discoloration Comparative Example 4 Bubbling, partial peeling, no discoloration
[0065] Test Example 3
[0066] Fire performance test, the results are shown in Table 3.
[0067] Table 3
[0068]
[0069] From the above analysis, the highly waterproof, corrosion-resistant and fire-retardant coating of the present invention has excellent fire resistance, high water resistance and corrosion resistance, and its physical and chemical properties meet national standards, and can achieve effective fire protection.
Claims
1. A highly waterproof and corrosion-resistant fire-retardant coating, characterized in that: Calculated by mass, it includes 20-25 parts of water-based epoxy resin, 10-15 parts of pure acrylic emulsion, 5-10 parts of polyurethane emulsion, 15-20 parts of organosilicon-modified ammonium polyphosphate, 8-10 parts of dipentaerythritol, 6-8 parts of melamine, 3-5 parts of graphene oxide-polyacrylic acid-nanosilica composite, 8-12 parts of pigments and fillers, 4-6 parts of zinc phosphate, 4-6 parts of additives and 8-10 parts of water.
2. A highly waterproof and corrosion-resistant fire-retardant coating according to claim 1, characterized in that: The graphene oxide-polyacrylic acid-nano silicon dioxide composite is prepared by the following method: S1. dispersing graphene oxide in deionized water, ultrasonically dispersing, to obtain a graphene oxide dispersion; adding a silane coupling agent thereto, stirring and reacting at 60-70° C. for 4-6 hours, to obtain graphene oxide treated with a silane coupling agent; S2. The graphene oxide treated with a silane coupling agent is dispersed in deionized water, a polyacrylic acid solution having a mass concentration of 5-7% is added, and the reaction is stirred at 60-70° C. for 6-8 hours to obtain a graphene oxide-polyacrylic acid composite; S3. Disperse nano-silica in deionized water and ultrasonically disperse it to obtain a nano-silica dispersion; disperse graphene oxide-polyacrylic acid complex in deionized water and ultrasonically disperse it to obtain a graphene oxide-polyacrylic acid complex dispersion, mix it with the nano-silica dispersion, stir and react at 60-70°C for 4-6h, centrifuge, wash with deionized water, and dry to obtain a graphene oxide-polyacrylic acid-nano-silica complex.
3. A highly waterproof and corrosion-resistant fire-retardant coating according to claim 2, characterized in that: The ultrasonic dispersion time is 1-2h.
4. A highly waterproof and corrosion-resistant fire-retardant coating according to claim 2, characterized in that: The amount of the silane coupling agent used is 1-2% of the mass of the graphene oxide.
5. The highly waterproof and corrosion-resistant fire-retardant coating according to claim 1, characterized in that: The pigment filler is selected from one or more of silicate, aluminum hydroxide, magnesium hydroxide, aluminum oxide, zinc borate, expanded graphite and nano clay.
6. A highly waterproof and corrosion-resistant fire-retardant coating according to claim 1, characterized in that: The auxiliary agent includes one or more of a thickener, a leveling agent, a dispersant, and a toughening agent.
7. A method for preparing a highly waterproof and corrosion-resistant fire-retardant coating, characterized in that: The following steps are involved: A. Premixing: Add water-based epoxy resin, pure acrylic emulsion, polyurethane emulsion and water into the reactor and stir evenly; B. Filler dispersion: add organosilicon-modified ammonium polyphosphate, dipentaerythritol, and melamine to the premixed solution, and stir at high speed; then add graphene oxide-polyacrylic acid-nanosilica composite, zinc phosphate, pigments and fillers, and additives to the premixed solution, and stir at high speed to obtain a coating; C. Filtration and packaging: Filter the prepared coating to remove impurities, and package and store.
8. The method for preparing a highly waterproof and corrosion-resistant fire-retardant coating according to claim 7, characterized in that: The stirring rate of high-speed stirring is 800-2000r / min, and the stirring time is 1-3h.
Citation Information
Patent Citations
Fireproof impact-resistant physicochemical plate special for laboratory table face
CN106084659A
High-strength anticorrosive water-based paint and preparation method thereof
CN107384084A
Fireproof coating with high-temperature resistance and preparation method of fireproof coating
CN108641551A
Coating liquid for photovoltaic backboard and photovoltaic backboard
CN114015296A
Cited By
Fireproof insulating paint and preparation method thereof
CN121950126A